Procession ends at the Sai Baba Temple - Mumbai Archive Project Team (Jio Institute, 2024)
The end-point of the procession is the Sai Baba Temple, located near Worli Fort. The open space in front of the temple is ideal for large gatherings. After a brief halt at the Sai Baba Temple, the procession starts the return journey to Papvimochneshwar Temple.